An Error Analysis of Subject-Verb Agreement on Students’ Descriptive Paragraph Writing at Babussalam Junior High School Pekanbaru - Robi Kurniawan; Abdul Rahman Firdaus (Nalar Global, 2020)
One of the problems that arises in English learning is the use of grammar. Subject-verb agreement is one of the basic rules in English, and the students still producing errors in producing it, especially in writing paragraphs. This research aimed to analyze errors of subject-verb agreement on students’ descriptive paragraph writing at Babussalam Junior High School Pekanbaru. The specific objective of this research was to know the types of errors and the most frequent type of errors on subject-verb agreement in descriptive paragraph writing made by the students. This research was descriptive qualitative research. The population of this research was the eighth-grade students which consisted of 5 classes. The total population of this research was 130 students. The researcher used Purposive Sampling Technique to take the sample. Thus, the researcher took 27 students as the sample of this research. In collecting the data, the researcher used a writing test to measure students’ error of subject-verb agreement in descriptive paragraph writing. The researcher analyzed the data by classifying the errors into the types of errors based on Surface Strategy Taxonomy by Dulay, Burt, and Krashen and making percentages for each type of errors. Based on the results, it was found that the errors of omission were 85 or 31.3%, the errors of the addition were 31 or 11.4%, the errors of misformation was 154 or 56.6%, and the error of misordering was 2 or 0.7%. Based on the research findings, it can be concluded that misformation is the most frequent type of error on subject-verb agreement in descriptive paragraph writing made by the eighth-grade students at Babussalam Junior High School Pekanbaru.